2017
DOI: 10.1057/s41265-016-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Trading and its Role in Fragmented Markets

Abstract: The financial services industry is among the leading industries in IT-spending. Still, little research exists which investigates how IT influences the financial services sector. Against this background, we study how a technology which emerged within the last years affects securities trading: High-Frequency Trading (HFT). Hereby, we focus on HFT and its impact on market efficiency. On the basis of a long-term analysis, we find that HFT decreases price dispersion among two distant markets. Analyzing the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Furthermore, research has shown that HFT facilitates price discovery by incorporating new information into prices more efficiently and by trading against transitory pricing errors (Brogaard et al 2014). Moreover, HFT technology improves price coordination across different markets by reducing costs and time to monitor and react to information from the different markets on which an asset is traded (Haferkorn 2017). Contrary to the majority of findings for equity markets, Lee (2015) finds no positive effects of HFT on liquidity and volatility in futures markets.…”
Section: The Effects Of Hft On Securities Marketsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, research has shown that HFT facilitates price discovery by incorporating new information into prices more efficiently and by trading against transitory pricing errors (Brogaard et al 2014). Moreover, HFT technology improves price coordination across different markets by reducing costs and time to monitor and react to information from the different markets on which an asset is traded (Haferkorn 2017). Contrary to the majority of findings for equity markets, Lee (2015) finds no positive effects of HFT on liquidity and volatility in futures markets.…”
Section: The Effects Of Hft On Securities Marketsmentioning
confidence: 94%
“…Menkveld (2013) finds that an often pursued strategy of HFTs is market making, i.e., to provide liquidity to the market on a continuous basis, allowing others to trade on the basis of efficient prices throughout the day. Moreover, due to their speed advantage, HFTs quickly incorporate new information into prices (Brogaard et al 2014) and coordinate prices across different venues (Haferkorn 2017). However, Accepted after 3 revisions by Dennis Kundisch.…”
Section: Introductionmentioning
confidence: 99%
“…Relying on emerging digital technologies combined with natural data advantages, digital enterprises use cutting-edge digital investment technologies and predictive models that are conducive to speculative arbitrage, such as: big data sentiment index, stock data visualization, AI market prediction system and highfrequency trading, etc. (Wurgler and Baker, 2006;Cooper et al, 2017;Haferkorn, 2017,), after the nancial market obtains massive information, it can mine high-return speculative targets and favorable speculative timing. At the same time, the application of digital technology has also optimized the risk assessment system of manufacturing companies, so that manufacturing companies can achieve the pro t-seeking goal of high pro ts and quick money within the controllable range of short-term risks.…”
Section: Digitalization Intensi Es the Nancialization Of Manufacturin...mentioning
confidence: 99%
“…Through the above paths, we can improve quality and increase e ciency, create new competitive advantages and pro t growth space for enterprises, and then guide enterprises to return to entity development and avoid "turning off the real and turning to the virtual". However, the application of cutting-edge digital investment technologies such as big data sentiment indexes and AI prediction systems can also provide technical support for companies investing in nancial assets that pursue high rates of return (Cooper et al, 2017;Haferkorn, 2017). At the same time, given that digital media transcends the categories of direction, distance and element connection de ned by traditional physical space, it further blurs the boundaries of corporate operations and reduces the risk of corporate cross-border investment (Chen Jian et al, 2020;Xue et al, 2022), and the characteristics of digital information such as multi-dimensionality, immediacy, zero distance, and easy copying also provide convenience for information transmission and imitation, which further intensi es the cohort effect of companies entering the nancial eld and enhancing nancialization (Zhang Jun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall effect is negligible in magnitude, hence the authors conclude that the legislation did not have a significant effect on market quality. On the other hand, Haferkorn () shows that price dispersion between trading venues has increased after the implementation of the German HFT Act, implying that market efficiency has improved due to the regulation.…”
Section: Changes In Regulations and Market Structure In Relation To Hmentioning
confidence: 99%